Evaluation of the Master’s Program in Curricula and Mathematics Teaching Methods at Taif University in the Light of Hammond’s Model - Al-Amri, Hamdan Aziz Ahmad; Al-Malki, Awad Saleh Saleh (Journal of Educational and Psychological Sciences, 2022)
The study aimed to evaluate the master’s program in curricula and methods of teaching mathematics at Taif University in the light of the Hammond model and to reveal the significance of the differences in the estimates of the sample responses due to the difference in the variable (professor-student), To achieve this, the researcher followed the descriptive analytical approach. The study tool was represented by a questionnaire prepared by the researcher, which included three axes distributed over (57) phrases, in the professors’ questionnaire, and (59) phrases in the students’ questionnaire, which were applied to (13) male and female students who are enrolled in the program for the academic year 1442-1443 AH, and (21) professors. The results indicated that the degree of practicing all dimensions of the study obtained an overall average (3.94 out of 5), i.e., to a (high) degree, and at the axes level; The material elements: (time period - equipment), a total average (3.88 out of 5), and secondly, the program elements (objectives - content - teaching methods - evaluation methods), with a total average (4.01 out of 5), and thirdly: the human elements (teachers - students) with a total average (3.93 out of 5) and to the absence of differences between the average estimates of the responses of (professors and students due to the difference in the variable (professor-student), and also indicated the success of the program in achieving its objectives, and that the reasons for success are due to the strengths after analyzing the qualitative questions in the questionnaire in the three dimensions In light of the results, the researcher presented a number of recommendations and suggestions for developing the program, in addition to proposals for future studies on the subject.